Oligodendrocytes regulate the adhesion molecule ICAM‐1 in neuroinflammation. Issue 3 (17th November 2021) - González‐Alvarado, María Nazareth; Aprato, Jessica; Baumeister, Melissa; Lippert, Magdalena; Ekici, Arif B.; Kirchner, Philipp; Welz, Tobias; Hoffmann, Alana; Winkler, Jürgen; Wegner, Michael; Haase, Stefanie; Linker, Ralf A.
Abstract: Recently, oligodendrocytes (Ol) have been attributed potential immunomodulatory effects. Yet, the exact mode of interaction with pathogenic CNS infiltrating lymphocytes remains unclear. Here, we attempt to dissect mechanisms of Ol modulation during neuroinflammation and characterize the interaction of Ol with pathogenic T cells. RNA expression analysis revealed an upregulation of immune‐modulatory genes and adhesion molecules (AMs), ICAM‐1 and VCAM‐1, in Ol when isolated from mice undergoing experimental autoimmune encephalomyelitis (EAE). To explore whether AMs are involved in the interaction of Ol with infiltrating T cells, we performed co‐culture studies on mature Ol and Th1 cells. Live cell imaging analysis showed direct interaction between both cell types. Eighty percentage of Th1 cells created contacts with Ol that lasted longer than 15 min, which may be regarded as physiologically relevant. Exposure of Ol to Th1 cells or their supernatant resulted in a significant extension of Ol processes, and upregulation of AMs as well as other immunomodulatory genes. Our observations indicate that blocking of oligodendroglial ICAM‐1 can reduce the number of Th1 cells initially contacting the Ol. These results suggest that AMs may play a role in the interaction between Ol and Th1 cells. We identified Ol interacting with CD4 + cells in vivo in spinal cord tissue of EAE diseased mice indicating that our in vitro findings are of interest to further scientific research in this field. Further characterization and understanding of Ol interaction with infiltrating cells may lead to new therapeutic strategies enhancing Ol protection and remyelination potential. Oligodendrocytes regulate immune modulatory genes and adhesion molecules during autoimmune neuroinflammation Oligodendrocytes interact with Th1 cells in vitro in a physiologically relevant manner Adhesion molecules may be involved in Ol‐Th1 cell interaction. Main Points: Oligodendrocytes regulate immune modulatory genes and adhesion molecules during autoimmune neuroinflammation. Oligodendrocytes interact with Th1 cells in vitro in a physiologically relevant manner. Adhesion molecules may be involved in Ol‐Th1 cell interaction.